316TiPNeoadjuvant and adjuvant pembrolizumab (pembro) plus standard of care (SOC) in patients (pts) with resectable locally advanced (LA) head and neck squamous cell carcinoma (HNSCC): The phase III KEYNOTE-689 study. (24th November 2019) - Cohen, E; Uppaluri, R; Lee, N; Westra, W; Haddad, R; Temam, S; Le Tourneau, C; Chernock, R; Safina, S; Tao, Y; Klochikhin, A; Meirovitz, A; et al.
Abstract: Background: Phase 2 studies (NCT02296684 and NCT02641093) with neoadjuvant and adjuvant pembro have demonstrated pathological response (PR) and acceptable safety in pts with high-risk resectable LA HNSCC. The randomized, global, open-label, phase 3 KEYNOTE-689 trial (NCT03765918) will evaluate the efficacy and safety of neoadjuvant pembro and adjuvant pembro plus SOC in pts with previously untreated resectable LA HNSCC. Trial design: Pts will be randomly assigned 1:1 to two arms. In arm A, pts will receive neoadjuvant pembro (200 mg Q3W, 2 cycles), followed by surgical resection, then SOC plus adjuvant pembro (200 mg Q3W, 15 cycles). In arm B, pts will undergo surgical resection followed by adjuvant SOC without pembro. SOC is radiotherapy (RT) alone (pts at low risk) or RT plus concurrent cisplatin (3 cycles of 100 mg/m 2 Q3W) (pts at high risk). RT is standard fractionation at 2 Gy/fraction for 30, 33, or 35 fractions (60 Gy, 66 Gy, or 70 Gy) for pts at low risk or high risk or with gross residual disease, respectively. Randomization will be stratified by primary tumor site (oropharynx/oral cavity vs larynx vs hypopharynx), tumor stage (III vs IVA), and HPV p16 status (oropharynx p16–positive vs oropharynx p16–negative or larynx/hypopharynx/oral cavity). Eligible pts are adults with newly diagnosed, resectable, nonmetastatic stage III/IVA HNSCC (AJCC Cancer Staging Manual, 8th edition), evaluable tumor burden, and ECOG PS 0 or 1 who are eligible for primary surgery. Treatment will continue until disease progression, unacceptable toxicity, or decision to withdraw in both arms. Co-primary end points are major PR (≤10% invasive SCC within resected primary tumor and sampled regional lymph nodes per blinded central pathology) and event-free survival. Secondary end points include overall survival, pathological complete response, quality of life, and safety. The first radiologic imaging in arm A will occur after 2 cycles of pembro and before surgery. Postoperative imaging will occur in both arms 12 weeks after SOC, then every 3 months until year 3 and every 6 months thereafter. Recruitment is ongoing; estimated enrollment is ∼700 pts. Clinical trial identification: NCT03765918. Legal entity responsible for the study: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Funding: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure: E. Cohen: Advisory / Consultancy: Amgen; AstraZeneca; Bayer; Bristol-Myers Squibb; Incyte; MSD; Merck. R. Uppaluri: Advisory / Consultancy, Research grant / Funding (self): Merck. N. Lee: Advisory / Consultancy: Merck, Merck Serono, Pfizer, Sanofi; Spouse / Financial dependant, Spouse Stockholder: AstraZeneca. W. Westra: Advisory / Consultancy, Travel / Accommodation / Expenses: Merck. R. Haddad: Advisory / Consultancy: Celgene, Merck, Eisai, Bristol-Myers Squibb, AstraZeneca, Pfizer, Loxo, Genentech, Immunomic Therapeutics; Research grant / Funding (institution): Boehringer Ingelheim, Merck, Bristol-Myers Squibb, Celgene, AstraZeneca, VentiRx, Genentech, Pfizer, Kura. C. Le Tourneau: Honoraria (self), Advisory / Consultancy: Merck Serono, Bristol-Myers Squibb, MSD, Amgen, Novartis, Nanobiotix; Travel / Accommodation / Expenses: Bristol-Myers Squibb, Amgen, MSD, Merck Serono. R. Chernock: Advisory / Consultancy: Merck, Roche. Y. Tao: Research grant / Funding (institution): Debiopharma, MSD, Pfizer; Travel / Accommodation / Expenses: MSD, Merck Serono. I. Brana: Advisory / Consultancy: Bristol-Myers Squibb; Speaker Bureau / Expert testimony: Bristol-Myers Squibb, AstraZeneca, Merck Serono; Research grant / Funding (self): AstraZeneca, Bristol-Myers Squibb, Celgene, Gliknik, GlaxoSmithKline, Janssen Oncology, Kura, Merck Sharp & Dohme, Novartis, Orion Pharma GmbH, Pfizer; Travel / Accommodation / Expenses: AstraZeneca Spain, Merck Serono. J.Y. Ge: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. R. Swaby: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc. B. Bidadi: Full / Part-time employment: Merck. D. Adkins: Advisory / Consultancy: Pfizer, Eli Lilly, Merck, Celgene; Travel / Accommodation / Expenses: Pfizer. All other authors have declared no conflicts of interest.